Thermal comfort, adaptability and sustainability of vernacular single family houses in Libya - Abdrahman Shahran; Darko Reba; Milena Krklješ (Tehnički Vjesnik, 2017)
Traditional and vernacular housing was developed in close relation between the functional needs of the occupants, the culture, climate, and other aspects of the living and built environment. Over the course of the last decades, most developing countries, including Libya, have experienced a rapid economic growth and increase in population, leading to the increase in construction of contemporary single family houses influenced by western models. The paper analyses aspects of thermal comfort in traditional single family houses in mountain (city of Gharyan) and desert regions (old city of Ghadames) in Libya with an aim to investigate advantages of the vernacular concepts in contemporary design. The study will establish valorisation criteria by researching structures, materials, internal arrangement, roof, openings and other aspects that influence sustainability. The results will be used in the fields of architecture, urban design and building industry in Libya, since the knowledge of traditional concepts and elements sustained through a long period of time will be valuable in building healthy homes and saving non-renewable energy in contemporary structures.